Globals of Completely Regular Monoids (Communications in Mathematical Research, 2021)
An element of a semigroup $S$ is called irreducible if it cannot be expressedas a product of two elements in $S$ both distinct from itself. In this paper we showthat the class $C$ of all completely regular monoids with irreducible identity elementssatisfies the strong isomorphism property and so it is globally determined.